PERANAN ISLAM DALAM PEMBANGUNAN PRADABAN DUNIA - Gunawan, Syafri (IAIN Padangsidimpuan, 2019)
The advancement of technology and science today is dominated by western scientitst so that many stents are developing that Islamic scientists are far behind Western scientists, making Muslim generations more idolizing Western scientists than Muslim scientists so that the pride of thesis, thesis and dissertation examines about the general sciences dominated by Western scientific book references and even nothing is sourced from Muslim scholars. So in this paper, the author wants to explain about Muslim scientific works which are quite popular in their time to know that even Muslim scientific works cannot be exploited in order to contribute to the development of world civilization.